Antibacterial activities of Sesbania grandiflora extracts - Anantaworasakul P. (2017)
In this study, Sesbania grandiflora, a plant in the Leguminosae family, was investigated for its antibacterial activities. The agar well diffusion assay as well as the agar and broth dilution assays were used for determination of antibacterial activities. The crude ethanolic extracts obtained from different parts of this plant exhibited different potent activities. The stem bark has the most potential to yield an extract with the highest antibacterial action. The fractionation of the stem bark with different solvents indicated that the fractionated extracts obtained from ethyl acetate or butanol possessed the most pronounced antibacterial activity. The kinetic study of bactericidal activities revealed that the butanol fractionated extract of the stem bark was effective against Gram negative bacteria. This study suggests that the stem bark of S. grandiflora contains promising antibacterial substances for clinical purposes. © 2011, International Research and Cooperation Association for Bio & Socio-Sciences Advancement. All rights reserved.